O debate sobre o federalismo na Assembleia Nacional Constituinte de 1933-34 - Souza, José Augusto Marques de (2021)
In this work, we analyze the constitucional process of the period 1933-34, questioning whether federalism was in fact a central dispute in the National Constituent Assembly and in the 1934 Constitution itself. Therefore, we have reconstructed the Brazilian constitutional trajectory and the period before the summoning of the constituent, examining the players and interests in dispute at those times, especially in the period immediately after the 1930’s Revolution when the conflict between the São Paulo primary-exporting elites and the Vargas project engaged together, more directly in conflict. In the first group, the emphasis was on the defense of decentralization and regionalism, while for the Government the post-1930 modernization process of the Brazilian State would require centralization, which brought with it expansion of state power, increase of industrialization, guarantee from labor rights to urban masses, institutional renewal, need for economic regulation and, above all, defense of a national project. The constituent process of 1933-34 amplified the debate, since it involved political players from all Brazilian states, getting close to the Government's arguments, sometimes to the São Paulo primary-exporting group. Given this context, the 1934 Constitution was the first one to deal with the Modern, dealing with themes that had not previously been discussed in the previous constituents. However, it did not last a long period, since it was soon replaced by the 1937 Constitution that inaugurated the authoritarian period of the Estado Novo. Based on this, our hypothesis is that the unresolved tensions in the constituent process of 1933-34 between the groups in favor of decentralization and the centralizing project may be the key to explain the brief decline of the 1934 Act, the twenty-two volumes of the Annals of the National Constituent Assembly of 1933-34, the Electoral Code of 1932, the preliminary draft of the Itamaraty Commission, the substitute of the Committee of 26 and the 1934 Constitution, mapping how the debate about federalism occurred in that period. Through this mapping, we highlight players, groups and speeches, concluding that, in fact, federalism was central to that constituent and that the contest between federalists and centralizers is structural to understand both the 1930-1934 context and the Constitution itself.